Resilience in Education: An Introduction - Beltman, Susan; Mansfield, C. (Springer, 2018)
Resilience. in. Education: An. Introduction. Susan Beltman and Caroline F. Mansfield Abstract This volume has arisen from burgeoning international interest in the field of resilience in a variety of educational contexts. It gathers together current ...